Surgical Treatment in Unstable Fractures of the Pelvis and Acetabulum in Children Under 3 Years (London Journal of Medical and Health Research, 2024)
The incidence of pelvic fracture represents between 0.5 to 1% of the total hospital admissions for pediatric trauma, in turn the acetabular fracture corresponds to one case per 100,000 children. This low presentation is due to the very special characteristics that this presents. bone segment that allows it to have great elasticity and great tolerance to trauma. We present two patients under three years of age with unstable type IV lesions in the modified classification of Torode and Zieg, who were managed surgically through open reductions and placement of osteosynthesis material. It is impossible to standardize management protocols in this age group, therefore the most appropriate thing is to adhere to pre-established treatment guidelines for skeletally mature people. Our objective is to highlight this type of high-energy injuries that occur with increasing frequency. regularity in very young patients and that on some occasions there will be the need, according to the fracture patterns, to perform the corresponding surgical stabilization to avoid major complications in the short, medium or long term.
Keywords: type 2 diabetes mellitus; diabetic nephropathy; P-selectin (CD62P); E-selectin (CD62E); kidney tissue biopsy; microvascular complications.; Hemodialysis; validation; Chronic kidney disease; Health-related quality of life; bolivia; latin america; Cross-cultural adaptation; patient outcomes; renal replacement therapy.; Surgery; Child; fracture; pelvic; acetabular